Economic Disparities Associated with Access to Endovascular Stroke Care in the United States. (16th November 2020) - Waqas, Muhammad; Levy, Bennett; Vakharia, Kunal; Aldstadt, Jared; Yasumiishi, Misa; Davies, Jason; Snyder, Kenneth V; Levy, Elad I; Siddiqui, Adnan H
Abstract: INTRODUCTION: Timely access to endovascular capable stroke center (ECC) is key to achieving optimal clinical and functional outcomes. Yet a large proportion of US population do not a have timely access to ECCs. METHODS: Accredited and state designated ECCs were included in the study. Geo-mapping of ECCs was performed. Census blocks (1 block = 2500 residents) were created using US census data. Percentage of patients with 60-minute access to an ECC facility was calculated using a previously validated methodology. Median household income data was obtained for each state. States were divided into 3 categories based on percentile household income. The difference in the percentage of population with access with 60-minute access to ECC was evaluated statistically. RESULTS: We included 316 ECCs in our analysis. Approximately 65% of all US residents have within one-hour access to a specialized stroke center by way of air or ground. In high-income states (median houselhold income >$76, 715), 69.0% of the population had one-hour access to ECCs. In the middle-income states (median household income $48, 486 to $76, 106), 49.5% of the population had one-hour access to ECCs, while only 21.4% residents of low-income states (median household income $43, 567 to $48, 392) one-hour access to TCCs, P -value = .01. Excluding Alaska, which does not currently have a TCC but has a median household income above 9 th percentile, 82.5% of the population in high-income states would have one-hour access to TCCs. This is demonstrated in. A positive and significant relationship between economic status and percentage population with one-hour access was observed (r = 0. 44, P -value = .01). CONCLUSION: Significant geographic and economic disparities exist between states with regards to access to ECCs. To ensure universal access to endovascular care in the US it is imperative to recognize and overcome these disparities.